Multi-scale modelling of the dynamics of natural aerosol plumes in Africa - (:unkn) unknown (My University, 2007)
The aim of this study was to document as precisely as possible the mass balance of desert dust, which is a major actor in the Earth's climate system as its annual mass flux is about half of the total aerosol annual flux. Recent studies revealed some cases difficult to model so that, in this work, we chose to focus on two key issues of North Africa: the Bodélé region, due to its complex local topography, and Sahelian tropical squall lines, the interactions of which with mineral dust remain largely unknown. This study was conducted at high mesoscale resolution using the Regional Atmospheric Modeling System (RAMS) coupled online with the Dust Production Model (DPM) developed by Marticorena and Bergametti [1995] and Laurent [2005]. In order to test the ability of this model to retrieve dust emissions in the complex area of the Bodélé, we first modelled the period corresponding to the Bodélé Dust Experiment 2005 (BoDEx 2005). Our model was able to reproduce the local meteorological features (mainly low level winds) and also the mineral dust concentrations and the structure of the plume observed during the experiment. Furthermore, we verified that mineral dust emitted from this region of the world reaches the South American continent. In addition, during this validation, we checked a modelling problem reported by several authors: General Circulation Models (GCMs) often fail when trying to represent wind fields in the Bodélé depression. Then, we undertook a climate study (on year 2001) over an extended area around the Bodélé region at several horizontal resolutions in order to characterize the low level phenomena that could explain the quasi-systematic bias of GCMs. This work was validated using the routine data of the ground-based stations as well as satellite imagery. The second case in which the validation of the model was necessary consisted in tropical squall lines that succeed in the Sah
Keywords: African Research